1998
DOI: 10.1177/004051759806800807
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrolytic and Chemical Treatment on the Mechanical Properties of Aramid and Copolyaramid Fibers

Abstract: Commercial PPTA fibers ( Kevlar 49® and Twaron 1055®) and copolyaramid fibers (Trevar®) are subjected to various hydrolytic and chemical treatments. Tensile modulus, tensile strength, and elongation at break are measured, and mechanical property deterioration is compared. Copolyaramid fibers show improved hydrolytic stability and chemical resistance compared to PPTA fibers. The time dependence of degradation processes can be described by two decreasing exponential functions. WAXS measurements detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 8 publications
6
38
1
1
Order By: Relevance
“…Springer et al7 evaluated the influence of basic and acid hydrolytic treatments on the mechanical properties of PPTA fibers. They showed that both modulus and tensile strength were affected, but the property drops were larger in acid and basic solutions than in a neutral environment.…”
Section: Introductionmentioning
confidence: 99%
“…Springer et al7 evaluated the influence of basic and acid hydrolytic treatments on the mechanical properties of PPTA fibers. They showed that both modulus and tensile strength were affected, but the property drops were larger in acid and basic solutions than in a neutral environment.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have studied the kinetics of hydrolysis of PPTA 12, 13. For example, Morgan et al12 established that the fiber strength degradation (Δ t ) increases with the time, relative humidity (RH), temperature, and applied load: where k t and K 5 are constants, E is the activation energy for hydrolysis, σ % is the applied stress expressed as a percentage of the fiber strength at time t , R is the gas constant, and T is the absolute temperature.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Riewald2 reported a 1.5% strength loss for Kevlar 29 and Kevlar 49 yarns after 1 year of immersion. Springer et al13 showed that the addition of 10% NaCl to pure water reduced the tensile strength degradation of Kevlar 49 fibers because of a shielding effect, whereas it remained unchanged for Twaron 1055 fibers. This latter point has not been explained.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 25% loss in tensile strength was observed when fibres were immersed for 15 s in a sulfuric acid bath of 80% concentration, whilst at 85% acid concentration, the loss in strength was around 35% [36]. Springer et al [37] noticed that the aramid fibre kept only 60% of its original strength value after treated by 40% sulfuric acid for one day. The acid hydrolysis of aramid is also observed by other researchers [38][39][40].…”
Section: Tensile Propertiesmentioning
confidence: 99%